PENERAPAN JUSTICE COLLABORATOR DALAM SISTEM PERADILAN PIDANA DI INDONESIA - Fadli Razeb Sanjani; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Justice Collaborator understanding in the general public often be confused with Whistle Blower, though equally to cooperate with law enforcement agencies to provide important information related to a legal case. But both have a different legal status, so that the two can not beequated. Granting the status of Justice Collaborator usually given for criminal acts which besifat organized and pose a serious threat to public safety issues and undermine democratic values. For example, corruption, terrorism, drugs, money laundering, or the Human Trafficking. The term Whistle Blower and Justice Collaborator now often appear in corruption cases handled by the Corruption Eradication Commission (KPK), the term both quoted from the Appellate Court (SEMA) No. 4 of 2011 on the treatment for the reporting crime (Whistle Blower) and witness the perpetrator collaboration (Justice Collaborator) in certain criminal acts. The purpose of the author discusses Justice Collaborator problem is due to the frequent occurrence of misperceptions in the community and also for its own law enforcement officials the authority of labeling a person can become a Justice Collaborator. Because after the author inventarisir that provisionJustice Collaborator is the authority of the judge and the judge examine certain criminal cases by the facts that occurred in the trial on the grounds that alleviate the burdensome and in accordance with Article 197 letter (f) of the Criminal Procedure Code and SEMA No: 04 Year 2011. Since that determines a person as the main perpetrator or who participate commit a specific criminal act is after the judges checked out and try the case in court, so if there are other institutions that determine a person as Justice Collaborator is an arbitrary act, it is author to convey because our country is a country of law is not a mere power in the sense that all that is done by law enforcementauthoritiesisbasedontheAct.Criminal Justice System which apply to the Justice Collaborator on the crime of corruption and certain other criminal offenses, are not regulated in detail it means not getting adequate arrangements to be a legal basis for law enforcement officers. Until now the setting of Justice Collaborator only explicitly stipulated in the Supreme Court Circular No. 4 of 2011 and regulations together on treatment for the reporting crime (Whistleblower) and a witness who cooperated (Justice Collaborator) in certain criminal cases, thus SEMA and the joint regulation has no binding legal force as well as the Act is internal in the sense that only the Supreme Court. Unlike the Code of Criminal Procedure law and Special Events are governed by laws that have been through the Special Similarly constitution stages in the formation of its legislation.Keywords: Justice Collaborator - corrupt - whistleblower – democratic - criminal